Assessment of genetically modified sugar beet H7‐1 for renewal of authorisation under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐006). (16th November 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐006 under Regulation (EC) No 1829/2003 from KWS SAAT SE and Monsanto Company, the Panel on Genetically Modified Organisms of the European Food Safety Authority (GMO Panel) was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the herbicide‐tolerant genetically modified sugar beet H7‐1. The data received in the context of this renewal application contained a systematic search and evaluation of literature, updated bioinformatics analyses and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequence of the event in sugar beet H7‐1 considered for renewal is identical to the originally assessed event, the GMO Panel concludes that there is no evidence in the context of this renewal application for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on sugar beet H7‐1.